دراسة حول مفهوم الوحدات المسبقة الصنع وتطبيقاتها في عملية إعادة الإعمار - أومري, أديب (Latakia University Journal -Engineering Sciences Series, 2016)
إن التصدي لمشكلة إيواء المتضررين نتيجة الكوارث سواء كانت طبيعية أو نتيجة الحروب التي نشهدها، هي من أهم التحديات التي تواجه العالم اليوم، كما أن نسبة هذا الضرر يكون كارثيا بالنسبة للدول النامية والفقيرة كونها ضعيفة الإمكانيات المادية وتعاني نقص كبير في الخبرات.لذلك كان لابد من دراسة هذه المشكلة على صعيدين الأول يبحث في تأمين مراكز الإيواء السريع كما في المخيمات وغيرها، أما الصعيد الأخر والذي يأتي في المرحلة الثانية ليكون إيواء أكثر أمنا وإنسانية. وهو اتخذ عدة حلول وإمكانيات مختلفة حسب الوضع والموارد الاقتصادية وهذا البحث سيتعرض إلى إحدى هذه الحلول وهي وحدات السكن المؤقت المسبق الصنع.Addressing the problem of harboring affected as a result of disasters, whether natural or the result of the wars that we are witnessing, Is one of the most important challenges facing the world today, The proportion of this damage will be catastrophic for the developing and poor countries Being weak material resources and suffers a great lack of experience.Therefore it was necessary to study this problem on the first two levels looking to secure the rapid evacuation centers, As in the camps and others, The other level, which comes in the second phase to be harboring a safer and more humane.It took several different possibilities and solutions according to the situation and economic resources, and this research will be subjected to one of these solutions, a temporary housing units and pre-made.